TERRITORIAL CHARACTERISTICS OF TRADITIONAL RESIDENTIAL BUILDINGS IN UZBEKISTAN (KHORAZM AND BUKHARA) (Journal of Universal Science Research, 2024)
In this article, the territorial characteristics of traditional residential buildings in Uzbekistan are highlighted on the example of traditional settlements of Khorezm and Bukhoro, mainly using natural methods to create a microclimate and develop regional architecture.